2023
DOI: 10.1021/acs.jpcc.3c03045
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Study of Solid–Solid Interfacial Reactions in All-Solid-State Batteries

Abstract: The sulfide-based solid-state electrolyte has garnered attention as a potential material for next-generation all-solidstate batteries. However, during cycling, interfacial reactions between the sulfide solid-state electrolytes and the cathode can occur, which is a serious issue that needs to be addressed. Therefore, resolving interfacial reactions has become a crucial issue in the development of solid-state batteries. A sulfide-based allsolid-state battery paired with LiFePO 4 has shown poor first-cycle discha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…A similar study was recently reported using Fe K-edge nXANES at the surface of LiFePO 4 in contact with a sulfide. 18 We also performed in situ piecewise EIS on (Li/In|Li 6 PS 5 Cl|NMC111/Li 6 PS 5 Cl) cells with 10 mg composite cathodes to study the evolution of impedances during cycling. This piecewise EIS allowed an estimation of the active surface area in a cell with uncoated NMC, which was 7.5× lower than the theoretical value.…”
mentioning
confidence: 99%
“…A similar study was recently reported using Fe K-edge nXANES at the surface of LiFePO 4 in contact with a sulfide. 18 We also performed in situ piecewise EIS on (Li/In|Li 6 PS 5 Cl|NMC111/Li 6 PS 5 Cl) cells with 10 mg composite cathodes to study the evolution of impedances during cycling. This piecewise EIS allowed an estimation of the active surface area in a cell with uncoated NMC, which was 7.5× lower than the theoretical value.…”
mentioning
confidence: 99%